PELATIHAN STRATEGI PENGERJAAN SOAL TKA BAHASA INGGRIS BAGI SISWA KELAS XII SMKN 3 KOTA SOLOK - Fitri Handayani; Risza Dwiputri; Riyen Permata; Zulfariati Zulfariati; Yuli Herman (PUAN INDONESIA, 2026)
This community service activity aimed to support the readiness of twelfth-grade students at SMKN 3 Kota Solok in preparing for the English Academic Ability Test (TKA). The activity was developed in response to several challenges identified during the preliminary needs analysis, including limited familiarity with TKA question formats, ineffective reading strategies, inadequate academic vocabulary, and difficulties in managing time during tests. An educative-participatory approach was implemented through interactive lectures, strategy demonstrations, guided practice, and collaborative discussion of test items. The training focused on practical test-taking strategies, including skimming and scanning techniques, identifying main ideas and keywords, eliminating implausible answer choices, and managing time effectively. Based on observations during the training, students’ practice activities, and participant reflections, the program indicated positive changes in students’ understanding of TKA question characteristics, the use of reading strategies, time-management awareness, and confidence in approaching literacy-based assessments. The findings suggest that explicit strategy instruction combined with authentic test simulation can provide meaningful learning experiences that support students’ academic and psychological preparedness for literacy-based assessments. The approach also offers a practical model for assisting vocational high school students in preparing for the English TKA.